2019
DOI: 10.3390/ijms20051241
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Phosphoproteome Analysis in TNF Long Term-Exposed Primary Human Monocytes

Abstract: To better understand the inflammation-associated mechanisms modulating and terminating tumor necrosis factor (TNF-)induced signal transduction and the development of TNF tolerance, we analyzed both the proteome and the phosphoproteome in TNF long term-incubated (i.e., 48 h) primary human monocytes using liquid chromatography-mass spectrometry. Our analyses revealed the presence of a defined set of proteins characterized by reproducible changes in expression and phosphorylation patterns in long term TNF-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Further, MAPK-phosphorylated Thr188 may act as a priming site for GSK3β-mediated phosphorylation of Ser184 and Ser179, i.e., phospho-residues favoring dimerization due to conformational changes and enhancing both DNA binding and transactivation activity [40,258]. Decreased C/EBPβ-Thr235 phosphorylation due to GSK3 inactivation was detected in TNF long-term-incubated monocytic cells in the presence of kenpaullone [259] as well as human monocyte-derived DC in response to platelet-activating factor [260]. In contrast, in IL-17-stimulated murine ST2 stromal cells, ERK-mediated priming phosphorylation at Thr188 and subsequent phosphorylation at Ser179 by GSK3 have been described as being repressive for certain C/EBP-dependent genes [261].…”
Section: C/ebp-associated Signalingmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, MAPK-phosphorylated Thr188 may act as a priming site for GSK3β-mediated phosphorylation of Ser184 and Ser179, i.e., phospho-residues favoring dimerization due to conformational changes and enhancing both DNA binding and transactivation activity [40,258]. Decreased C/EBPβ-Thr235 phosphorylation due to GSK3 inactivation was detected in TNF long-term-incubated monocytic cells in the presence of kenpaullone [259] as well as human monocyte-derived DC in response to platelet-activating factor [260]. In contrast, in IL-17-stimulated murine ST2 stromal cells, ERK-mediated priming phosphorylation at Thr188 and subsequent phosphorylation at Ser179 by GSK3 have been described as being repressive for certain C/EBP-dependent genes [261].…”
Section: C/ebp-associated Signalingmentioning
confidence: 95%
“…In addition, GSK3 inhibition in TNF-tolerized cells also results in increased binding of p65 at the promoters of tolerizable genes (e.g., IL-6), reduced expression of A20 (a negative regulator of NF-κB signaling, e.g., during TNF incubation [291]), and enhanced chromatin accessibility [288]. Recently, it has further been demonstrated that numerous proteins differentially phosphorylated under conditions inducing high-dose TNF tolerance are potential GSK3 targets [259]. However, further analyses have to elucidate whether additional GSK3-dependent mechanisms are involved in the complex regulation of tolerance formation and the termination of pro-inflammatory signaling.…”
Section: Inhibition Of Gsk3 and The Perpetuation Of Inflammationmentioning
confidence: 99%
“…Preparation of whole-cell and nuclear extracts, determination of protein concentrations, electrophoresis, and Western blotting were performed as described: 20 , 27 cells were lysed in extraction buffer P (8 M urea, 4% 3-[(3-Cholamidopropyl)-dimethylammonio]-propane-sulfonate (Sigma-Aldrich), 30 nM Tris, 1% Nonidet P-40 (AppliChem, Darmstadt, Germany), 1% HALT phosphatase inhibitor (Thermo), and EDTA-free cOmplete protease inhibitor (Sigma-Aldrich) cocktails). To obtain nuclear proteins, cells were additionally sonicated (10 s, 20% power; Bandelin, Berlin, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent (phospho-)proteome analysis of long-term TNF-incubated monocytic cells suggests that glycogen synthase kinase (GSK) 3 represents a crucial kinase regulating the phosphorylation status and associated molecular functions orchestrating the termination of inflammation-induced signaling. 20 In addition, by controlling the activation of various transcription factors including NF-κB and C/EBP, GSK3 is strongly involved in the transcriptional regulation of gene expression. 21–23 GSK3 consists of two highly similar paralogues (α and β) and is predominantly controlled via inhibitory phosphorylation at Ser21 (GSK3α) or Ser9 (GSK3β) by kinases such as protein kinase (PK)Cα and β or PKB/Akt.…”
Section: Introductionmentioning
confidence: 99%
“…The TNF pathway is a pivotal proinflammatory signaling cascade that relies heavily on protein phosphorylation, the extent of which has been revealed by phosphoproteomic studies (Wagner et al, 2016, Mohideen et al, 2017, Zhong et al, 2014, Krishnan et al, 2015, Welz et al, 2019, Cantin et al, 2006). Much is already known about key mechanistic events and we briefly recapitulate those that are pertinent to our study.…”
Section: Introductionmentioning
confidence: 99%